Analysis Affecting The Human Development Index In Central Java Province 2018-2022 - Puteri Ayu Kharisma; Maulidyah Indira Hamarini (Universitas Muhammadiyah Makassar, 2024)
The development of a country requires special attention to Human Resources (HR) as the main element of development. This article aims to examine the influence of Population, Unemployment, Gross Regional Domestic Product (GRDP), and Poverty on the Human Development Index (HDI) in Central Java Province for the 2018-2022 period. The research method used is quantitative with secondary data and uses a panel data approach. The data involves 29 districts and 6 cities in Central Java Province in the 2018-2022 period. The dependent variable is HDI, while the independent variables include Population, Unemployment, GRDP, and Poverty. Panel data regression analysis was carried out using the Common Effects Model (CEM), Fixed Effects Model (FEM), and Random Effects Model (REM) approaches, as well as the Chow test and Hausman test for selecting the best model. The research results show that population has a positive effect on HDI, because a large population creates economies of scale and increases people's purchasing power. Unemployment also has a positive influence on HDI, due to the existence of frictional unemployed who look for work according to their level of education. GRDP shows a positive and significant influence on HDI, in accordance with Kuznet's theory of economic growth. However, poverty does not have a significant effect on HDI. Future research is recommended to consider more independent variables and expand the research time span.